EXTENDED LAND RIGHTS GOVERNANCE AND SUPERVISION: A LITERATURE REVIEW TOWARDS SUSTAINABLE LAND USE AND PROTECTION OF THE RIGHTS OF SURROUNDING COMMUNITIES - Yustinus Lambang Setyo Putro; Siti Nur Azizah; Gunawan Widjaja; Dyah Ersita Yustanti (Adisam Publisher, 2025)
This study aims to examine the governance and supervision of extended land rights in the context of sustainable land use and the protection of the rights of surrounding communities. Through a literature review, this study analyses the regulations, administrative mechanisms, and supervisory practices applied in Indonesia regarding the extension of land rights, particularly Building Use Rights (HGB) and Cultivation Use Rights (HGU). This study highlights challenges such as legal uncertainty, administrative barriers, and lack of community participation, which have the potential to trigger conflicts and hinder sustainable land use. Furthermore, this study integrates environmental and social sustainability principles into the management of land rights extension, with a focus on protecting the rights of surrounding communities, particularly indigenous peoples and local communities with traditional tenure rights. Effective monitoring, involving technology and active community participation, is key to achieving fair, productive, and sustainable land use. This study provides policy recommendations based on the principles of good governance to promote transparent, accountable, and inclusive governance. The results of this study are expected to serve as a basis for stakeholders in formulating policies and practices for land tenure extension that not only guarantee legal certainty but also support sustainable development and social protection. Thus, this study contributes to strengthening a land tenure system that is responsive to current and future needs.